Sensitivity and specificity of Cobas TaqMan MTB real-time polymerase chain reaction for culture-proven Mycobacterium tuberculosis: meta-analysis of 26999 specimens from 17 Studies - Horita, Nobuyuki (Nature Publishing Group, 2015)
Since 2010, studies on the diagnostic accuracy of COBAS TaqMan MTB (CTM) have been frequently reported with an unignorable discrepancy. The key inclusion criterion for this systematic review was original studies that could provide sufficient data for calculating the sensitivity and the specificity of CTM for M tuberculosis (TB) or M tuberculosis complex. The reference test was Mycobacterium culture. We used bivariate model for meta-analyses. Of the 201 candidate articles, we finally identified 17 eligible articles.Concerning the respiratory specimens, 1900 culture positive specimens and 20983 culture negative specimens from 15 studies were assessed. This provided the summary estimate sensitivity of 0.808 (95% CI 0.758–0.850) and the summary estimate specificity of 0.990 (95% CI 0.981–0.994). The area under curve was 0.956. The diagnostic odds ratio was 459 (95% CI 261–805, I2 26%). For the smear positive respiratory specimens, the sensitivity was 0.952 (95% CI 0.926–0.969) and the specificity was 0.916 (95% CI 0.797–0.968). For the smear negative respiratory specimens, the sensitivity and the specificity were 0.600 (95% CI 0.459–0.726) and 0.989 (95% CI 0.981–0.993), respectively. The diagnostic accuracy was poorer for the non-respiratory specimens, than for the respiratory specimens, but was acceptable. We believe that the information obtained from this study will aid physicians’ decision making.